1C.12: DIETARY SALT INTAKE AND ALDOSTERONE-RELATED ORGAN DAMAGE IN HYPERTENSION. (June 2015) - Catena, C.; Colussi, G.; Brosolo, G.; Martinis, F.; Pezzutto, F.; Nait, F.; Sechi, L.A.
Abstract : Objective: Chronic exposure to elevated aldosterone levels results in cardiac and renal tissue injury with mechanisms that are independent of blood pressure levels. Although the interaction between dietary salt intake and circulating aldosterone in causing organ damage has received support in animal experiments, the evidence of this interaction in the clinical setting is much weaker. In this study we have investigated the relevance of dietary salt on aldosterone related cardiac and renal damage in primary hypertension. Design and method: In 315 untreated, grade1–2, hypertensive patients (age 47 ± 13 yr.; 173 males) we measured anthropometric variables, general biochemistries, plasma active renin and aldosterone levels, glomerular filtration rate, and 24-hour urinary sodium (UNaE) and albumin excretion (UAE), and assessed cardiac morphology and function by B-mode echocardiography. Secondary forms of hypertension were excluded by exhaustive examination in all patients. For statistical reasons, patients were subdivided into tertiles or quartiles according to their UNaE that was used as a measure of salt intake. Results: UAE increased progressively across tertiles of UNaE and patients with plasma aldosterone levels above the median of the distribution (125 pg/ml) had significantly higher UAE than patients with lower levels in all tertiles of UNaE. Search for statistical interaction between plasma aldosterone and UNaE in the association with UAE, however, did not reveal interaction. Left ventricular mass index (LVMI) was significantly greater in patients with plasma aldosterone levels above the median than patients with lower levels, but no change of LVMI was observed across quartiles of UNaE. LV geometry and ejection fraction did not differ across quartiles of UNaE and were comparable in patients with high or low plasma aldosterone levels. Both UAE and LVMI were significantly and independently related with age, body mass index, systolic blood pressure, and plasma aldosterone. UNaE was significantly related with UAE, but this relationship was lost after correction for confounders. Conclusions: In summary, circulating aldosterone contributes to subclinical renal and cardiac damage in primary hypertension, but its contribution is independent of dietary salt intake.